PENEGAKAN HUKUM PEMERINTAHAN TERHADAP PELAKSANAAN HIBURAN MALAM DI KOTA PEKANBARU TAHUN 2022 (STUDI KASUS HIBURAN MALAM GOLD DRAGON) - Fikri, Zackiul; ', Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
In this research, there are several problematic phenomena raised in 2022 regarding Government Law Enforcement regarding the Implementation of Nightlife in Pekanbaru City in 2022 regarding the public's unrest regarding the "Gold Dragon" nightlife venue which is still operational until the early hours of the morning and has committed many violations of regulations. Pekanbaru City Regional (PERDA) Number 13 of 2021 concerning Public Order and Community Peace. So the public asks the Civil Service Police Unit (Satpol PP) and the Government to carry out strict and intensive supervision in monitoring the abundance of nightlife in Pekanbaru City which is currently thriving. So this role is of course the authority of the Government for Satpol PP in supervising and implementing applicable law enforcement. Not only that, the imposition of sanctions, administrative fines, revocation of business permits for business owners (night entertainment) must be even stricter and the sanctions greater in order to have a deterrent effect on these business actors. This research is descriptive research with a qualitative approach. The types of data used are primary data and secondary data, primary data is obtained directly from informants, while secondary data is data that supports or strengthens primary data. Data collection techniques were carried out by means of interviews and documentation. The results of this research show that Government Law Enforcement and the Implementation of Satpol PP's duties in controlling night entertainment businesses in the City of Pekanbaru, especially the "Gold Dragon" night entertainment, are running as they should, but there are deficiencies in the work process carried out by the Pekanbaru City Satpol PP starting from the actions taken. continuation of the reports received, there is a lack of supervision over night entertainment, so the Government's role in enforcing existing laws must be stricter, starting from Revocation of Licenses or Sealing of Businesses, Imposing Sanctions, and Administrative Fines. Keywords: Government Law Enforcement, Pekanbaru City Satpol PP.